Idiopathic venous thrombosis - Haas, S. (Hämostaseologie, 2006)
Idiopathic venous thromboembolism has been shown to be associated with a high frequency of recurrence. Therefore, the most important aim of long-term treatment is secondary prevention. It has also been shown that long-term anticoagulation with vitamin K antagonists can impressively reduce the rate of recurrence. However, this effect was only maintained during anticoagulation and disappeared after cessation of anticoagulant therapy. Unfortunately, the individual risk of recurrence is not predictable. Therefore, longterm anticoagulation appears beneficial across all subgroups of patients suffering from venous thromboembolism, regardless of the presence of thrombophilia or other burden of the disease. Despite the increasing body of evidence regarding the advantages of long-term anticoagulation, bleeding complications may limit the net clinical benefit of this strategy. Thus, the development of anticoagulants having a low potential for adverse reactions and providing similar beneficial antithrombotic effects to vitamin K antagonists will enhance the readiness for their wide spread use and life long administration.
Keywords: Venous thromboembolism; long-term anticoagulation; secondary prevention; deep vein thrombosis; pulmonary embolism